The Early Findings of an Urban Education Teacher Preparation Program: A Case Study - Terry, Alice W.; Head, Catherine (Educational (Re)naissance, 2013)
A university near a major city in Georgia and a large, urban school district established a Professional Development School (PDS) in which the majority of junior and senior-level pre-service teacher coursework and fieldwork took place at seven urban, high-needs public schools. The purpose of this study was to provide preliminary feedback to the middle grades teacher preparation program concerning the UE (Urban Education) program in preparation for the second cohort of UE interns and the second year of study with the first cohort. What emerged from the study was evidence that the program, for its participating teacher candidates, leads to commitment, strengthens self-efficacy, and fosters early development of teacher efficacy, but which ultimately evolves into teacher candidate overconfidence. As pressure continues to mount concerning the quality of education in America, teacher preparation programs must improve their programs in order to better prepare teachers for diverse classrooms. This study relates one such effort toward that end.